Formulasi Dan Uji Mutu Fisik Dari Granul Effervescent Ekstrak Daun Salam (Syzyginum polyanthum) - Dewi, Ni Luh Samila; Suradnyana, I Gede Made; Juliadi, Debby (Usadha, 2024)
Bay leaf is one plant that has benefits as traditional medicine, acting as an antioxidant with flavonoid content. The processing is still very simple, which has an impact on the short shelf life of the herb. One alternative to prevent this is to formulat e bay leaf extract into effervescent granule preparations, which provide a more comfortable feeling with a large concentration of active substances. This study aims to determine the difference in the physical quality of effervescent granule preparations wit h variations of effervescent salts and to determine the concentration of acids and bases that produce effervescent granules of bay leaf extract with good physical quality. In 3 effervescent granule preparation formulas, the variation in acid and base concentrations (citric acid, tartric acid, and sodium bicarbonate) is F1 by 9.4%; 18.7%; 27%, F2 by 8.6%; 17.2%; 29%, and F3 by 7.9%; 15.8%; 31%. Physical quality evaluation of effervescent granule preparations includes organoleptis, flow velocity, rest angle, disperse time, pH, and moisture content. Quantitative data were analyzed with the One Way Anova test to determine the difference in physical quality of the three effervescent granule preparation formulas. Based on the results of physical quality tests, the three greenish-white granule formulas were obtained, the characteristic smell of bay leaf extract, and the granule form with a flow speed of 10 g / second, a stati onary angle in the range of 31-35 °, a dispersion time of < 5 minutes, a pH in the range of 5-6, and a moisture content of < 5 minutes. The results of One Way Anova testing found that the three formulas with variations of effervescent salts have different physical qualities, and acid-base concentrations that produce good physical qualities, namely F1 and F3